ANALISIS RESIKO HIPOKRISIS DALAM GAYA KEPEMIMPINAN DI LAPAS KLAS IIB PAYAKUMBUH - Rifqi Mufadhol Masand; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
Hypocrisis is a trait that is not good for a person to have. This hypocrisy means that there is a mismatch between words and actions or it can be said that a person's thoughts, hearts, and actions are not in harmony. The risk posed by this hypocrisy is very disturbing to the welfare of the surrounding environment. Moreover, in the environment of an organization that has a leader. Leaders who have this hypocritical nature in order to make the environment around the organization a bad risk. This study aims to determine the risk caused by the Hypocrisis in the leadership style of an organization. The method used in this research is a qualitative method in which research data is obtained by direct observation to the field and conducting interviews with informants.